Therapeutic hypothermia for stroke: Unique challenges at the bedside - You, Je Sung; Kim, Jong Youl; Yenari, Midori A. (Frontiers in Neurology, 2022)
Therapeutic hypothermia has shown promise as a means to improving neurological outcomes at several neurological conditions. At the clinical level, it has been shown to improve outcomes in comatose survivors of cardiac arrest and in neonatal hypoxic ischemic encephalopathy, but has yet to be convincingly demonstrated in stroke. While numerous preclinical studies have shown benefit in stroke models, translating this to the clinical level has proven challenging. Major obstacles include cooling patients with typical stroke who are awake and breathing spontaneously but often have significant comorbidities. Solutions around these problems include selective brain cooling and cooling to lesser depths or avoiding hyperthermia. This review will cover the mechanisms of protection by therapeutic hypothermia, as well as recent progress made in selective brain cooling and the neuroprotective effects of only slightly lowering brain temperature. Therapeutic hypothermia for stroke has been shown to be feasible, but has yet to be definitively proven effective. There is clearly much work to be undertaken in this area.